Efectos de la aplicación del Programa de Enriquecimiento Instrumental sobre un grupo de jóvenes infractores - William R. Avendaño Castro; Abad E. Parada Trujillo; Esperanza Casadiego Rivera (Revista Criminalidad)
The objective of this research was to analyze the effects of applying Reuven Feuerstein’s Instrumental Enrichment (FIE) Program to a group of juvenile offenders during a resocialization process by Fundación El Faro in the municipality of San José of Cúcuta, Colombia. It corresponds to a qualitative, descriptive study framed within the epistemological orientation of the interpretative paradigm. Ten young people with various characteristics and limitations participated in the resocialization process. Virtual relationship instruments, comparisons and FIE spatial relationships were used in the intervention and for information collection, along with the field log. The results presented from a qualitative perspective show a set of changes in the cognitive structures of young people subject to intervention. That is, cognitive functions and mental operations changed, although some factors limited mediation, such as psychoactive substance consumption and the environment within the rehabilitation center. The evidence allows concluding that the Mediated Learning Experience (MLE) and the program’s cognitive potentials are significant, as indicated in other studies on the different environments in which the Structural Cognitive Modifiability Theory is applied.